1994
DOI: 10.1128/aac.38.4.848
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibilities of bacterial isolates from patients with cancer to levofloxacin and other quinolones

Abstract: The antibacterial activity of levofloxacin was compared with those of ofloxacin and ciprofloxacin against bacterial isolates from patients with cancer. In general, levofloxacin was as active or was twofold more active than ofloxacin and was two-to fourfold less active than ciprofloxacin against most gram-negative pathogens. Against Pseudomonas aeruginosa, ciprofloxacin was the most active agent tested (MIC for 90% of isolates tested, 1.0 jig/ml). Overall, all three agents had similar activities against gram-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 17 publications
4
20
0
Order By: Relevance
“…Levofloxacin (a broad-spectrum fluoroquinolone) is the optically active L isomer of the racemate ofloxacin. Levofloxacin has activity against gram-negative bacteria similar to that of ciprofloxacin or ofloxacin and has a greater potency in vitro against gram-positive bacteria (8,10,24).…”
mentioning
confidence: 99%
“…Levofloxacin (a broad-spectrum fluoroquinolone) is the optically active L isomer of the racemate ofloxacin. Levofloxacin has activity against gram-negative bacteria similar to that of ciprofloxacin or ofloxacin and has a greater potency in vitro against gram-positive bacteria (8,10,24).…”
mentioning
confidence: 99%
“…In vitro studies suggest that it is approximately twice as active as ofloxacin (3) and, compared with ciprofloxacin, has similar or enhanced activity against gram-positive organisms (3,5,9).…”
mentioning
confidence: 99%
“…In the present study, the activity of levofloxacin was comparable to or greater than that of ciprofloxacin on the majority of gram-negative organisms tested. Dholakia et al [16] found levofloxacin to be two to four times less active than ciprofloxacin against gram-negative bacterial isolates from cancer patients. Although quinolone resistance in a variety of species, such as staphylococci, enterococci, and Pseudomonas spp., has been recognized for some time, levels of resistance in E. coli were extremely low [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Dholakia et al [16] found levofloxacin to be two to four times less active than ciprofloxacin against gram-negative bacterial isolates from cancer patients. Although quinolone resistance in a variety of species, such as staphylococci, enterococci, and Pseudomonas spp., has been recognized for some time, levels of resistance in E. coli were extremely low [16][17][18]. However, recent European reports revealed that quinolone resistance of E. coli is increasing in neutropenic patients who had received fluoroquinolones as prophylaxis [19,20].…”
Section: Discussionmentioning
confidence: 99%